Application of indocyanine green–human serum albumin complex in fluorescence image-guided laparoscopic anatomical liver resection: study protocol for a randomized controlled trial - Qingyun Xie; Fengwei Gao; Xiaoyun Ran; Xin Zhao; Manyu Yang; Kangyi Jiang; Tianyang Mao; Jiayin Yang; Kun Li; Hong Wu (Trials)
Abstract Background Indocyanine green (ICG) is a near-infrared fluorescent dye widely used for intraoperative navigation during liver surgeries because of its non-radioactive nature, high safety, and minimal impact on liver function. However, variability in its dosage and concentration and its low imaging success rates have limited its widespread application. To address these issues, we developed a novel ICG–human serum albumin (ICG-HSA) complex to enhance fluorescence visualization during laparoscopic anatomical liver resection. Methods This prospective, double-blind, single-center, randomized controlled trial will compare the fluorescence navigation effects of the novel ICG-HSA complex with the guideline-recommended ICG administration scheme. The study will involve patients aged 18 to 75 years with malignant liver tumors. The participants will undergo evaluations at specified time points, and data will be collected using an internet-based electronic data capture system. The primary outcome will be the effectiveness of intraoperative fluorescence imaging, assessed by three independent experts. The secondary outcomes will be conversion to open surgery, the total operative time, intraoperative blood loss, and long-term survival rates. Discussion The aim of using this novel ICG-HSA complex will be to improve the success rate of fluorescence navigation in liver resection by ensuring better stability and a longer liver retention time compared with free ICG. This study seeks to validate the clinical value of ICG-HSA in enhancing surgical precision and outcomes, ultimately promoting its broader clinical application. The results are expected to provide high-level evidence supporting the safety and efficacy of this new fluorescence imaging agent. Trial registration ClinicalTrial.gov NCT06219096. Registered on 1 December 2024.